A miR-150/TET3 pathway regulates the generation of mouse and human non-classical monocyte subset. Issue 1 (December 2018) - Selimoglu-Buet, Dorothée; Rivière, Julie; Ghamlouch, Hussein; Bencheikh, Laura; Lacout, Catherine; Morabito, Margot; Diop, M'boyba; Meurice, Guillaume; Breckler, Marie; Chauveau, Aurélie; Debord, Camille; Debeurme, Franck; et al.
Abstract Non-classical monocyte subsets may derive from classical monocyte differentiation and the proportion of each subset is tightly controlled. Deregulation of this repartition is observed in diverse human diseases, including chronic myelomonocytic leukemia (CMML) in which non-classical monocyte numbers are significantly decreased relative to healthy controls. Here, we identify a down-regulation of hsa-miR-150 through methylation of a lineage-specific promoter in CMML monocytes. Mir150 knock-out mice demonstrate a cell-autonomous defect in non-classical monocytes. Our pulldown experiments point to Ten-Eleven-Translocation-3 (TET3) mRNA as a hsa-miR-150 target in classical human monocytes. We show that Tet3 knockout mice generate an increased number of non-classical monocytes. Our results identify the miR-150/TET3 axis as being involved in the generation of non-classical monocytes. A decrease in the fraction of non-classical monocytes is a hallmark of chronic myelomonocytic leukaemia. Taking advantage of this abnormal situation, the authors identify a mechanistic link between miR-150 and TET3 as being involved in monocyte subset generation.